Child Healthy Education and Deep Education - Ganiyeva Dilnoza Farkhodovna (Central Asian Journal of Literature, Philosophy and Culture, 2022)
In the article below, the author discusses problems of children's health education and deep education. Life will certainly put a child through trials no matter what. Whatever it is - a sharp change in temperature, or an infection, or physical stress, or mental anguish, or excitement, a strong organism will respond to it with appropriate reactions.